If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -7x + 6x + -5 = 4 Reorder the terms: -5 + -7x + 6x = 4 Combine like terms: -7x + 6x = -1x -5 + -1x = 4 Solving -5 + -1x = 4 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + -1x = 4 + 5 Combine like terms: -5 + 5 = 0 0 + -1x = 4 + 5 -1x = 4 + 5 Combine like terms: 4 + 5 = 9 -1x = 9 Divide each side by '-1'. x = -9 Simplifying x = -9
| 2x-9+3x+1=4x+2-3x-5 | | -1n=2n-3 | | (2x-3)+4=15 | | 8+5*7= | | -2x+120=y | | 2y-16=4x | | 8y-2y+16=40 | | 74=x^3 | | y=-2(x-6) | | (7x-2)37=437 | | 73=x^3 | | 12+5=k+49 | | 88-16b=-16b+88 | | 78=-9-3(-56+12x) | | -x^2+10x+22=0 | | 7x-12=-36-11 | | logx=3.45 | | (y+2)/2-(2y-6)/3=1 | | 47-4m=7-12m | | 38.2x+41.7-12.9x-43.3= | | 77=4-10y+3 | | 8+x=14-2x | | -60x^2+5=0 | | -7w-3w+4w=-15 | | -19+7=12 | | -12(a-12)=-50 | | 8g+20=76 | | 8+x=12-2x | | 7(1+7m)=7+6m | | 21-3(2-a)=-12 | | 8+x=13-2x | | 15x-30(x+4)=9(x-25) |